1995
DOI: 10.1103/physreva.52.433
|View full text |Cite
|
Sign up to set email alerts
|

Secondary-electron emission from porous solids

Abstract: Porous structure can strongly change the electric behavior of material submitted to bombardment by energetic electrons: strong electric fields (10 V/m) can grow within the pores, because of the small sizes of these pores. We give a model of porous material that enables us to emphasize and illustrate the enhancement of the yield of secondary-electron emission (and the broadening in frequency of its profile) in a porous medium, compared to that in bulk material. Here we have considered materials of astrophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The results suggested that from a porous surface when SEE level increases, an important electron emission process from the ZC occurs due to the accumulation of charged particles near the pores [20]. These ionization electrons (β-electrons) which are produced in the walls of pores may enhance the SEE coefficient and such an enhancement would lead to a lowering of U B and reflected in the increase in the I -V characteristics [6].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that from a porous surface when SEE level increases, an important electron emission process from the ZC occurs due to the accumulation of charged particles near the pores [20]. These ionization electrons (β-electrons) which are produced in the walls of pores may enhance the SEE coefficient and such an enhancement would lead to a lowering of U B and reflected in the increase in the I -V characteristics [6].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that, from a porous surface when secondary electron emission (SEE) level increases, an important electron emission process from the ZC has become due to the accumulation of charged particles near the pores. 24 These ionization electrons (β-electrons) which produced in the walls of pores may enhance the SEE coefficient and that such an enhancement would lead to a lowering of the U B and reflected in the increase of the I-V characteristics. 7 This is based on the increase of the electric field in porosity.…”
Section: Investigation Of Conductivity Properties Of the Gas Dischargmentioning
confidence: 99%
“…The surface behavior caused by ionic or activated plasma species from discharge space is crucial to determine the ignition voltage needed to initiate the discharge and to define the operation limit of voltage required to sustain the discharge, and also to understand and explain the phenomena on the surface, such as the SEE. 24 ionization electrons (β-electrons) produced in the walls of pores by the incident ionizing radiation is accelerated in the pores by the applied electric field. These electrons produce emission electrons in the walls of other pores, which are in their turn accelerated in the pores, emitting new electrons.…”
Section: Secondary Electron Emission Processesmentioning
confidence: 99%
“…(6) and (7), which give a better description of the experimental data, rather than the Whiddington's law. The elementary theory has also been used to investigate the influence of the porosity on the electron-induced secondary-electron emission (Millet and Lafon, 1995). While the porosity effect on the secondary electron emission from dust grains can be revised in the framework of the present model, this is beyond the scope of this paper.…”
Section: Validity Of the Present Modelmentioning
confidence: 99%